Determinants of Savings and Community Loans in Ngawi District, 2010 - 2018 A Macro Economic Approach - Pradata, Yusnardhi Indra; Sarungu, JJ.; Suryantoro, A. (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims to analyze (1) the effect of income on community savings; (2) the effect of savings interest on community savings; (3) the effect of savings on community lending (4) the effect of loan interest on community lending; (5) the influence of external funds on community lending; (6) the right theory is applied in order to increase the receipt of savings and lending to the people of Ngawi Regency. This research is a type of quantitative research. The unit of analysis in this study is inter-time development data on the amount of savings and public loans, the determination of the interest rates for savings and loans on average per year, external funds, and income in Ngawi Regency during 2010-2018. Data analysis techniques using multiple linear regression in the form of log-linear. The results of the study found that: (1) Revenue did not have a real impact on the savings of the people of Ngawi Regency. (2) The determination of savings interest does not support the receipt of savings from the people of Ngawi Regency in BRI and Bank Jatim. (3) Savings can increase community loans in Ngawi Regency. (4) The policy for determining loan interest rates carried out at BRI and Bank Jatim is less able to have a real impact on the distribution of loans to the people of Ngawi Regency. (5) External funds are able to encourage the fulfillment of Ngawi Regency community loan disbursement. (7) Savings and less interest can be used to increase the savings and loans of the people of Ngawi Regency. This shows that the right theory applied to increase the receipt of savings and lending Ngawi Regency is Keynes's theory